Control on Carbonate Sedimentation of Tacipi Formation, South Sulawesi, Indonesia - N. Alit Ascaria (Berita Sedimentologi, 1998)
South Sulawesi is located in the centre of a complex tectonic region where Indo-Australian, Eurasian and Paific plates interact and collide. The Tacipi Formation was deposited during the middle Miocene to early Pliocene in an intra-arc or fore-arc setting. Facies distribution, diagenesis and hydrocarbon potential of these carbonate was strongly influenced by the tectonostratigraphic setting, faulting, subsidence and relative sea level changes.